Plantabilidade de sementes de soja classificadas por largura - Rodrigues, Claiton (2012)
The change in the profile of soybean varieties which favor the reduction of population is accompanied by the necessity of enhancement in the process for classifying seeds by size, standardizing the distribution in the sowing row. The present study aimed to characterize the classification of soybean seeds by size with the purpose of precision sowing. The first experiment conceptualized sorted lots at intervals of 0.5mm, 1.00mm, and unrated by size. To that end, the retention in the dominant sieve and number of diameters found in each of the intervals evaluated were used as parameters. In the second experiment combinations of intervals of classification by size of 0.5mm, 1.00mm, and unrated by size with different seed base diameters in a soybean cultivar. 5.0mm, 5.5mm, 6.0mm, and 6.5mm diameters were used. We evaluated the percentage of sowing at normal spacing, double spacing, spacing at failure, spacing at double failure, average spacing, number of seeds per linear meter, and population per hectare. A speed of 6.5km/hr was set for evaluation and desired sowing density of 14 seeds per linear meter. In the Experiment 3 the same parameters of the Experiment 2 were evaluated, but in four different soybean cultivars. The equipment used in the Experiments 2 and 3 to evaluate the plantability was Corn Counter from Syngenta. In the Experiment 4 the evaluation involved 182 samples of soybean seed lots collected in the warehouses of seeds buying companies. A quality assessment of classification by seed company size from Brazil, Paraguay, Argentina, saved grains, and Sementes Iruña company was done. All samples were subjected to sieving retention test. RDS parameters, number of sieves, and the percentage participation of each seed diameter. Based on the results, the following conclusions were drawn: the classification of soybean seeds by size favors plantability, showing lower rates of double sowing, failures and double failures, and a better distribution in lower spacing that favors a better fit in the sowing density. The classification in the range of 0.5 mm favors the plantability indexes with high retention in the dominant sieve, and favoring the choice of sowing disks. The great majority of seeds producing companies from Brazil, Paraguay, and Argentina have no rigor in seed classification by size classification.